Esensi Mutu Pendidikan Dalam Membangun Ekonomi Generasi Masa Depan - Rifki Alam (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
Education should be a priority subsector of the regional government development agenda. The acceleration of education development that touches all aspects and dynamics of education is expected to be able to raise the quality of education. This phenomenon encourages the need for a study to improve the quality of education in the process of economic development in Indonesia, because economic development is actually an integration of the dynamics of social, economic and institutional aspects. Education development in the regions must be fair, participatory and integrated, so that the current quality gap can be resolved in the not too distant future. This research was conducted in a descriptive analysis and supported by normative data and materials for the implementation of education at Yadika Senior High School in Bandar Lampung. The purpose of this research is to contribute solutions to the constraints of high costs and also to improve the essence of the quality of education in order to produce quality human resources ready to meet the competition in the world of work and the importance of the quality of education in the economic development of Indonesia's future generations. The Covid-19 pandemic has made online bullying a necessity. The role of the central government, local governments, and private education providers is needed to solve the problem of online learning during a pandemic so that the quality of education is maintained. Pandemic conditions also brought many positive lessons. Among other things, the adaptation of the use of technology in learning encourages the growth of extraordinary creative and positive energy. With the spirit of mutual cooperation and cooperation between education stakeholders to ease the burden on each other during the pandemic, it must be maintained and maintained so that the role of education in the economic development of the nation's future generations is guaranteed.